VD_FINDINFO Décision / 2013 / 684 vom 19. Juli 2013 - VD Tribunal cantonal (2013)
DÉTENTION PRÉVENTIVE, RISQUE DE COLLUSION, MENACEDROIT PÉNAL, SOUPÇON, RISQUE DE RÉCIDIVE | 221 al. 2 CPP (CH), 221 CPP (CH), 222 CPP (CH), 393 al. 1 let. c CPP (CH)